Molecular epidemiology of multidrug resistant tuberculosis in Mongolia and Eastern Siberia: two independent dissemination processes for dominant strains - S. N. Zhdanova (Sankt-Peterburg : NIIÈM imeni Pastera, 2021)
Mongolia and Russia are among the countries with the high tuberculosis (TB) burden. The prevalence of tuberculosis, including multidrug-resistant tuberculosis (MDR), in Eastern Siberia bordering Mongolia is significantly higher than in the European part of Russia. In addition, unlike Mongolia, Eastern Siberia is characterized by a high prevalence of HIV infection. The cross-border spread of socially significant infections in these countries seems to occur due to their wide-range cooperation and cultural exchange. Whereas the HIV infection has no epidemiological significance for Mongolia at the moment, tuberculosis, however, has a similar prevalence on both sides of the border. The aim was to evaluate the cross-border MDR M. tuberculosis distribution in Mongolia and Eastern Siberia by using molecular genetic data. Materials and methods. A total of 1045 M. tuberculosis strains isolated in Mongolia (291) and the three regions of Eastern Siberia (754) were studied by using the MIRU-VNTR-24 loci genotyping. The CC2/W148 and CC1 subtypes were identified by the specific deletion in the kdpD gene and SNP in the pks17 gene at position 1887060, respectively. Phylogenetic analysis of MIRU-VNTR patterns was carried out by generating UPGMA tree and maximum likelihood tree. Results. The Beijing genotype was found in 75.3% (219/291) and 69.0% (520/754) from Mongolian and East Siberian collection, respectively. Common minor genotypes were LAM (11.0% and 15.1%), T (10.3% and 4.5%), and Haarlem (1.4% and 2.4%) found in Mongolia and Eastern Siberia, respectively. The genotypes S (1.3%) and Ural (5.0%) were found solely in the Russia-derived samples. The main epidemic Beijing subtypes in each country belonged to different clonal complexes (CC): the majority of Mongolian Beijing strains displayed profiles 342-32, 3819-32, 1773-32 MLVA types and belonged to the CC4 subtype; Russian Beijing strains mainly belonged to the CC1 (43.7% — 227/520) and CC2/W148 (34.8% — 181/520) subtypes. The MDR level and distribution patterns differed significantly between Mongolia and Eastern Siberia. Modeling of Beijing strain expansion evidences about extremely subtle contribution of the M. tuberculosis cross-border transmission between Mongolia and Russia. The phylogenetic reconstruction of Beijing CC4 subtype evolution in Mongolia suggests that its distribution is primarily associated with China and other countries of the Western Pacific Region. Three main phylogenetic branches of CC4 subtype were traced, which probably spread throughout Mongolia in the 11—12th centuries. It may be assumed that spreading of the epidemic Beijing CC4 subtype might occur in two stages: early period — emergence of ancestral CC4 variants in Mongolia or their introduction from China (they are homologous to the strains preserved in the Chinese population), later period — dissemination due to the active exchange of M. tuberculosis with countries of Southeast Asia, but not Russia. Conclusion. Using MIRU-VNTR-24 genotyping as well as classification according to specific single nucleotide polymorphisms specific to certain Beijing subtypes, it allowed to describe separate patterns of the epidemic variants spread in Mongolia and Russia. It has been demonstrated that emergence and spread of MDR-TB in Mongolia are entirely iatrogenic in nature, while the epidemic subtypes of the Beijing genotype (subtypes CC1 and CC2/W148) contribute markedly into the MDR-TB spreading in Eastern Siberia.